Synthesis of zirconia/polyethylene glycol hybrid materials by sol–gel processing and connections between structure and release kinetic of indomethacin. (December 2014) - Catauro, M.; Bollino, F.; Papale, F.; Pacifico, S.; Galasso, S.; Ferrara, C.; Mustarelli, P.
Abstract Controlled and local drug delivery systems of anti-inflammatory agents are attracting an increasing attention because of their extended therapeutic effect and reduced side effects. In this work, the sol–gel process was used to synthesize zirconia/polyethylene glycol (ZrO2/PEG) hybrid materials containing indomethacin for controlled drug delivery. Different percentages of PEG were introduced in the synthesis to modulate the release kinetic and an exhaustive chemical characterization of all samples was performed to detect the relationship between their structure and release ability. Fourier transform spectroscopy and solid-state NMR show that the Zr–OH groups of the inorganic matrix bond both the ethereal oxygen atoms of the polymer and the carboxylic groups of the drug. X-ray diffraction analysis ascertains the amorphous nature of those materials. Scanning electron microscopy detects the nanostructure and the homogeneous morphology of the synthesized materials. The bioactivity was demonstrated by the formation of a hydroxyapatite layer on the surface of the samples, after soaking in a simulated body fluid. The release kinetics study, performed by HPLC UV–Vis spectroscopy, proves that the release ability depends on PEG and the drug amount and also demonstrates the indomethacin integrity after the synthetic treatment.